MOBILE LEARNING PADA MATA KULIAH STRATEGI PEMBELAJARAN MI/SD: PENELITIAN PENGEMBANGAN - Nur Hidayah Hanifah; Imam Rofiki; Agung Sedayu; Mokhamad Amin Hariyadi (Ta'dib, 2020)
There has been a trend of utilizing mobile tools in the university. This study is proposed to construct mobile learning media based on Android for Madrasah Ibtidaiyah or Primary School in Learning Strategy courses. The study participants were university students of Madrasah Ibtidaiyah Teacher Education in Malang. The study design was R and D with both quantitative and qualitative data. The study result have been in the form of mobile learning media based on Android. Six expert judgments have validated this product to ascertain the feasibility of the designed prototype. The validation by material experts' validation results were 91% and 89% valid, while validation rates by design experts were 93% and 92%. The validation result by learning experts showed 88% and 89% valid. The design was tested to three students with individual trials, then to a small group trial with ten students, and finally, a field trial on an experimental class of 43 students using a questionnaire. The trials' result on small groups showed 88% valid, and the field trials showed 86% valid. The findings indicated that Android-based mobile learning on learning strategy course material had a better effect than conventional learning on student learning outcomes.